Гігієнічна оцінка впливу забруднення атмосферного повітря на стан здоров'я дітей в умовах промислового міста - Кірсанова, Олена Валентинівна; Kirsanova, E. V. (My University, 2006)
Наведено нові дані щодо ранніх, донозологічних змін здоров'я дітей віком 7 - 10 років за умов високого рівня атмосферного забруднення, обумовленого викидами металургійної промисловості на підставі вираженості зрушень рівня функціонування, ступеня напруження регуляторних механізмів, функціональних резервів в індикаторній системі організму, якою є серцево-судинна система. Уперше визначено диференційований ступінь значущості забруднення атмосферного повітря, медико-біологічних і соціально-побутових чинників у виникненні донозологічних порушень здоров'я та виявлено чинники ризику їх виникнення у молодших школярів, мешканців одного з найбільших індустріальних центрів України - Запоріжжя. Розроблено заходи щодо охорони повітряного середовища, збереження та покращання здоров'я дітей даного регіону. Dissertation is devoted to study of the state of the health junior schoolchildren, dwelling in conditions atmospheric air pollution in the large industrial cities (on the example Zaporozhye). The work presents a evaluation of the atmospheric air pollution, biological and social factories which determine of background state of the organism children. Their health is estimated according to the indices physical development, state functional cardiovascular system and adaptation possibilities of the body. The degree and character of the dependents of children’s health on certain atmospheric air pollution, 58 biological and social factors have been determined. The risk factors most important for the formation of their predonosological health have been revealed. The measures for preserve and improve of the health in junior schoolchildren have been grounded. The principle results of this study will lay down the foundation for an increased efficacy of medical care for junior schoolchildren reflected in an improved population health dwelling in conditions contemporary large industrial cities.
Hygienical Evaluation Influence of Atmospheric Air Pollution on the State of the Health in Conditions Industrial Cities
Keywords: молодші школярі; забруднення атмосферного повітря; донозологічна діагностика; адаптація; профілактика; junior schoolchildren; atmospheric air pollution; predonosological diagnostics; adaptation; prevention